Preservasi Semen Kambing Peranakan Etawa dalam Pengencer Tris dan Sitrat Kuning Telur dengan Penambahan Sodium Dodecyl Sulphate (THE PRESERVATION OF ETTAWA GRADE BUCK SEMEN IN TRIS AND CITRATE EGG YOLK DILUENTS SUPPLEMENTED WITH SODIUM DODECYL SULPHATE) - Hidayati, Nur; Arifiantini, Raden Iis; Sajuthi, Dondin (Jurnal Veteriner; Vol 16 No 3 (2015), 2015)
This study was conducted to determineSDS concentration also to compare Tris egg yolk and citrateegg yolk on the quality of ettawa grade chilled semen. The study consist of two experiments. The firstexperiment was to determine the best SDS concentration in Tris egg yolk diluents and the second experimentwas to compare the SDS suplementation in tris and citrate egg yolk in the quality of ettawa grade chilledsemen. The semen were collected from three bucks, immediately after collection the semen evalutedmacro and microscopycally. Semen demonstrate more than 70% motility and less than 10% spermatozoaabnormality, individually divided into four tube, each tube was diluted in egg yolk supplemented with 0;0,025; 0,05; and 0.075% SDS then stored at 5°C for 72 hours. The quality of chilled semen was observefor motility and viability every 12 hours. Result demonstrated that 0.05% SDS was the best concentrationcompared to others. In the second experiment,the semen were diluted in four different diluents, it wereTris egg yolk (TEY), Tris egg yolk with 0.05% SDS (TEYS), citrate egg yolk (CEY) and citrate egg yolk with0.05% SDS (CEYS). Result demonstrated that the mean value of motility and viability of spermatozoa inTEYSdiluents (67.08 ± 6.43% and77.07 ± 6.78%) was higher (p<0.05) than CEYS (60.42 ± 9.05% and72.31± 7.45%), TEY (59.23 ± 9.41% and71.21 ± 8.56%) and CEY (53.45 ± 11.33% and67.74 ± 8.90%). In conclusion,supplementation of 0.05% SDS in TEY was maintained best sperm quality compared to other diluentsduring preservation.
Keywords: SDS, ettawa grade buck semen, liquid semen, tris-egg yolk, citrate-egg yolk